2008
DOI: 10.1002/jctb.1921
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous sulfide and acetate oxidation under denitrifying conditions using an inverse fluidized bed reactor

Abstract: BACKGROUND: Simultaneous removal of sulfur, nitrogen and carbon compounds from wastewaters is a commercially important biological process. The objective was to evaluate the influence of the CH 3 COO − /NO 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
2
21
1
3
Order By: Relevance
“…lactate, was found to be necessary, regardless of the initial concentrations of nitrate or nitrite [82]. Meanwhile, at a CH 3 COO − /NO − 3 molar ratio of 0.72 with a constant S 2− /NO − 3 molar ratio of 0.13, the efficiencies of nitrate, acetate and sulphide consumption were 100%, with N 2 and sulphate as the end products, and when more organic carbon was added sulphide was partially oxidized to elemental sulphur [83]. The competition between autotrophic and heterotrophic denitrifiers was quantitatively described and the degree of inhibition of sulphide on heterotrophic denitrifiers was realized based on the framework of Activated Sludge Model No.…”
Section: Reduced Sulphur Compoundsmentioning
confidence: 86%
“…lactate, was found to be necessary, regardless of the initial concentrations of nitrate or nitrite [82]. Meanwhile, at a CH 3 COO − /NO − 3 molar ratio of 0.72 with a constant S 2− /NO − 3 molar ratio of 0.13, the efficiencies of nitrate, acetate and sulphide consumption were 100%, with N 2 and sulphate as the end products, and when more organic carbon was added sulphide was partially oxidized to elemental sulphur [83]. The competition between autotrophic and heterotrophic denitrifiers was quantitatively described and the degree of inhibition of sulphide on heterotrophic denitrifiers was realized based on the framework of Activated Sludge Model No.…”
Section: Reduced Sulphur Compoundsmentioning
confidence: 86%
“…Oxidation of sulfide by chemolithoautotrophic denitrifying bacteria can lead to the formation of elemental sulfur or sulfate, depending on the environmental conditions (Beristain- Cardoso et al 2008;Cardoso et al 2006;Krishnakumar et al 2005;Wang et al 2005). Wang et al (2005) observed that elemental sulfur production was obtained at sulfide/ nitrate molar ratio in the range of 1.66-2.5 and sulfide concentrations less than 300 mg l -1 .…”
Section: Lithotrophic Denitrificationmentioning
confidence: 97%
“…Just as the organotrophic denitrification allows the simultaneous elimination of nitrate and organic compounds, the lithotrophic denitrification can eliminate simultaneously nitrate and reduced inorganic sulfur compounds such as sulfide, thiosulfate, and elemental sulfur (Cardoso et al 2006;Sierra-Alvarez et al 2007;Zhang et al 2008b). Nevertheless, it is possible to have a litho-organotrophic denitrification where both organic and inorganic compounds are used as energy sources (Beristain-Cardoso et al 2008;MezaEscalante et al 2007;Oh et al 2001;Reyes-Avila et al 2004). Electrons originated from organic matter and reduced sulfur compounds oxidation are transferred to nitrate instead of oxygen in order to build up a proton motive force usable for ATP regeneration (Schmidt et al 2003).…”
Section: Denitrification Processmentioning
confidence: 98%
See 1 more Smart Citation
“…Positive attributes for anaerobic biotreatment include elimination of the aeration cost and safety concerns associated with treatment of gaseous streams under rich oxygen environments, and possibility of simultaneous removal of sulphide and nitrate. The latter is important as nitrate is a major water contaminants causing severe environmental problems such as eutrophication, emission of greenhouse gases and acidic deposition, as well as health problems in human and animals (Beristain-Cardoso et al, 2008;Jing et al, 2009).…”
Section: Introductionmentioning
confidence: 99%